On the relationship of repair actions and patterns on bug localization approaches: a comparative study - Dias, Júlia Manfrin; Maia, Marcelo de Almeida (Anais do Workshop de Visualização, Evolução e Manutenção de Software (VEM), 2023)
In the evolving field of automatic program repair, bug localization approaches play an important role, given their potential to significantly narrow down the search range for potential solutions. Given the diversity of bug locating approaches and their respective performance variations, this study aims to evaluate the bug localization accuracy, considering specific characteristics of the bugs, defined by actions and repair patterns observed in patches. Repair actions constitute changes made to the code to derive a suitable solution to a given problem. These actions can range from additions, deletions, and alterations in the source code lines. Repair patterns, on the other hand, are generalized representations of recurrent action structures in the fixed code. We evaluate the accuracy of each bug locator with respect to these actions and repair pattern to identify if there are any influence of specific actions and/or patterns in each type of locator.